2011
DOI: 10.4061/2011/985703
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Comorbid Conditions among Middle-Aged and Elderly Hemophilia Patients: Prevalence Estimates and Implications for Future Care

Abstract: Introduction. Advances in hemophilia care and treatment have led to increases in the life expectancy among hemophiliacs. As a result, persons with hemophilia are reaching an older age and experiencing various age-related health conditions never seen before in this population. Aim. To determine the prevalence of comorbidities among middle-aged and elderly hemophilia A and hemophilia B patients. Methods. Retrospective chart review among all hemophilia patients, who attended the Gulf States Hemophilia and Thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
0
23
1
Order By: Relevance
“…They also found the prevalence of respiratory diseases, including asthma, to be 11% among these patients. 1 In the current study population, however, a lower prevalence of asthma (0.5%) was found. This could be, as mentioned before, related to the differences in the baseline characteristics of the populations in the two studies as Khleif et al included older patients who would naturally have more comorbidities.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…They also found the prevalence of respiratory diseases, including asthma, to be 11% among these patients. 1 In the current study population, however, a lower prevalence of asthma (0.5%) was found. This could be, as mentioned before, related to the differences in the baseline characteristics of the populations in the two studies as Khleif et al included older patients who would naturally have more comorbidities.…”
Section: Discussioncontrasting
confidence: 65%
“…Khleif et al determined the prevalence of chronic renal disease to be 8% in their study. 1 Renal function in patients of the current study was not determined using a specific test, and this needs further evaluation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…To complicate the picture many will not suffer from just one disease; they will, on average, be managing up to five co-morbidities by the age of 65 [4]. This does not include the side effects of diabetes, such as blindness due to diabetic retinopathy, or the complications of insulin management with multiple drugs to control cardiovascular disease.…”
Section: Introductionmentioning
confidence: 98%
“…In fact, the most recent review [1] concluded that the current life expectancy of haemophilia patients has approached that of males in the general population. Increasingly, age-related co-morbidities including cardiovascular disease, hypertension, diabetes, cancer, renal disease and overweight/ obesity have been described in the PWH [2][3][4][5][6], but joint arthropathy remains the main co-morbidity [3,6].…”
Section: Introductionmentioning
confidence: 99%